Intestinal tumors in neurofibromatosis 1 with special reference to fatal gastrointestinal stromal tumors (GIST) - Heli Ylä-Outinen; Niina Loponen; Roope A. Kallionpää; Sirkku Peltonen; Juha Peltonen (WILEY, 2022)
Background Type 1 neurofibromatosis (NF1) is a genetic tumor predisposing Rasopathy. NF1 patients have an increased risk for developing benign and malignant tumors, but the occurrence of intestinal tumors has not been investigated at the population level.
Methods In this retrospective register-based total population study, diagnoses of gastrointestinal tract tumors were retrieved from the Finnish Care Register for Health Care for 1,410 NF1 patients and 14,030 reference persons. We also reviewed the death certificates of 232 NF1 patients who died during years 1987-2013, and specifically searched for diagnosis of gastrointestinal stromal tumor (GIST).
Results The register analysis revealed an increased overall hazard ratio (HR) of 2.6 (95% CI 1.9-3.6) for intestinal tumors in NF1 compared to general population. The highest HR of 15.6 (95% CI 6.9-35.1) was observed in the small intestine. The focused analysis of NF1 death certificates and GISTs demonstrated that the GIST was the primary cause of death in seven patients.
Conclusion This study emphasizes the need for careful evaluation of NF1 patients with gastrointestinal complaints. The challenge in diagnosis is that the tumors preferably occur at the small intestine, which is difficult target for diagnostic procedures. We also show that the NF1 GISTs may lead to fatal outcome despite of benign histopathological findings at the time of the diagnosis.